2018
DOI: 10.7759/cureus.2492
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Xanthogranulomatous Cholecystitis: Master of Disguise

Abstract: A 67-year-old woman presented with clinical symptoms, radiological findings, and preoperative work-up highly suggestive of advanced stage IV carcinoma of the gallbladder (CG). An extended cholecystectomy with the excision of adjacent liver segments and loco-regional lymphadenectomy was performed. Final pathology results revealed diffuse xanthogranulomatous cholecystitis (XG) with ruptured Rokitansky-Aschoff sinuses with tumor-resembling adenomyosis without atypical or malignant cells. There was a reactive infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Rupture of Rokitansky-Aschoff sinuses, small mucosal ulcerations, gallstones, and presence of bacteria in the bile eliminated by macrophages may play a role in this serious inflammation. Furthermore, XGC has benign histological features but a severe clinical picture; in addition, it is clinically important due to difficulty in its differentiation from gallbladder cancer (6).…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of Rokitansky-Aschoff sinuses, small mucosal ulcerations, gallstones, and presence of bacteria in the bile eliminated by macrophages may play a role in this serious inflammation. Furthermore, XGC has benign histological features but a severe clinical picture; in addition, it is clinically important due to difficulty in its differentiation from gallbladder cancer (6).…”
Section: Discussionmentioning
confidence: 99%
“…XGC is a poorly understood and rare gallbladder disease that can mimic gallbladder cancer. There are several theories about pathophysiology, but the most widely cited one hypothesizes that increased intraluminal pressure in the gallbladder causes extravasation of bile into the gallbladder wall which is then taken up by activated histiocytes and fibroblasts causing a granulomatous reaction followed by cellular immune response and fibrosis [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Establishing the correct diagnosis of XGC remains challenging, especially when the inflammatory process involves the surrounding tissues, the diagnoses is frequently delayed until the final pathology results [4]. Waskin et al [6] studied multi detector CT as an imaging modality to detect XGC and showed a moderate sensitivity but poor specificity for differentiation of XGC from gallbladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although XGC is not an exceptional fnding, direct involvement of extra-gallbladder organs/multivisceral structures like the colon, duodenum, and right hepatic artery is very rare, with only a few cases reported in the literature [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%